Nazal kavite ve osteomeatal kompleks anatomik varyasyonları - Akif Sumbullu; Binali Cakur; Dogan Durna; Oguzhan Altun (Cumhuriyet University, 2013)
Objectives: The maxillary sinuses are important anatomical structures for dental procedures in dentistry. The normal function of the sinuses is effective in the success of these dental procedures. The continuation of the normal functions of the paranasal sinuses, the maxillary and osteomeatal complex (OMC) has an important role. In this study, we aimed to investigate the frequency of osteomeatal complex anatomic variations with cone-beam computed tomography. Material and Methods: In this retrospective study, in cone-beam computed topographies of 280 patients (154 men, 126 women), anatomic variations of paranasal sinuses (deviated septum, inferior turbinate hypertrophy, concha bullosa, paradoxical middle turbinate, Agger nasi, Haller's cell, Onodi cell, pneumatized uncinate process (uncinate bulla), pneumatized crista galli, pneumatized septum) were analyzed. Results: In our study, septal deviation 85%; inferior turbinate hypertrophy 48.6%; middle concha bullosa 40%; Agger nasi cells 28.6%; Haller's cells 9.6%; pneumatized septum 4.6%; paradoxical middle turbinate 2.5%; pneumatized uncinate process 2.5%; pneumatized crista galli 1.4%; Onodi %1.1 were found. Conclusion: Variations of the osteomeatal complex due to the effect of the paranasal sinuses should be considered in maxillary dental implant planning. Keywords: Anatomic variation, osteomeatal complex, cone-beam computed tomography.   ÖZETAmaç: Diş hekimliğinde maksiller sinüsler dental girişimler için önemli anatomik yapılardır. Bu girişimlerin başarısında sinüslerin normal fonksiyonları etkilidir. Maksiller ve diğer paranazal sinüslerin normal fonksiyonlarını sürdürmesinde osteomeatal kompleks (OMK) önemli bir role sahiptir. Bu çalışmada nazal fossa ve osteomeatal kompleks anatomik varyasyonlarının konik ışınlı bilgisayarlı tomografi (KIBT) ile sıklığının araştırılması amaçlandı. Gereç ve Yöntem: Bu retrospektif çalışmada 280 hastanın (154 erkek, 126 kadın) konik ışınlı bilgisayarlı tomografilerinde paranazal sinüslerin anatomik varyasyonları (Agger nazi hücresi, Haller hücresi, Onodi hücresi, orta konka bulloza, paradoksal orta konka, pnömatize unsinat proses (uncinate bulla), pnömatize krista galli, pnömatize septum, alt konka hipertrofisi, septum deviasyonu) incelendi. Bulgular: Çalışmamızda septum deviasyonu %85; alt konka hipertrofisi %48.6; orta konka bulloza %40; Agger nazi hücreleri %28.6; Haller hücreleri %9.6; pnömatize septum %4.6; paradoksal orta konka %2.5; unsinat proses pnömatizasyonu %2.5; pnömatize krista galli %1.4; Onodi hücresi %1.1 olarak bulundu. Sonuç: Osteomeatal kompleks varyasyonları paranasal sinüslere olan etkisi nedeniyle maksiller dental implant planlamalarında dikkate alınmalıdır.